Betulia liberata azione sacra in due parti, K. 118 - Mozart, Wolfgang Amadeus 1756-1791; Metastasio, Pietro 1698-1782 (Aparté Music, Little Tribeca, 2020)
"Composed in 1771 to a libretto by Metastasio tracing the well-known biblical story of Judith and Holofernes, Betulia liberata was Mozart's first oratorio. The Assyrians have led siege on Bethulia, and its people is losing hope that the city will be freed. Judith, a beautiful and deeply religious widow, succeeds in penetrating the enemy camp and seduces Holofernes, before killing him during his sleep. Often described as a stroke of genius, Betulia liberata shows the dramatic intensity of which he was already capable at the age of just fifteen and the influence of his early experiences with opera" --Provided by publisher
Interpreten: Sandrine Piau (Amital). Amanda Forsythe (Cabri/Carmi). Teresa Iervolino (Giuditta). Pablo Bemsch (Ozìa). Nahuel Di Pierro (Achior). Accentus. Les Talens Lyriques. Christophe Rousset (Dirigent)
Aufnahme: Boulogne-Billancourt, Juni 2019
Keywords: CD